To the freemen of Pennsylvania : the proposed extension of the excise law in this province, has for some days been the subject of conversation in almost every company . - Mifflin, Thomas, 1744-1800 ([publisher not identified], 1772)
Broadside to the freemen of Pennsylvania which is critical of a proposed extension of an excise tax.